2005
DOI: 10.1007/s10327-005-0226-z
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic relationships between the lettuce root rot pathogen Fusarium oxysporum f. sp. lactucae races 1, 2, and 3 based on the sequence of the intergenic spacer region of its ribosomal DNA

Abstract: The genetic relationship between the vegetative compatibility groups (VCGs) and between physiological races of Fusarium oxysporum f. sp. lactucae (FOL), the causal pathogen of lettuce root rot, was determined by analyzing the intergenic spacer (IGS) region of its ribosomal DNA. A total of 29 isolates containing a type strain were tested: 24 Japanese isolates, 2 Californian isolates, and 3 Italian isolates. Three races (races 1, 2, and 3) were found in Japan, and race 1 was also distributed in California and It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 21 publications
0
28
0
Order By: Relevance
“…Although the IGS rDNA has become one of the most popular loci for investigating genetic diversity within the FOSC (Fujinaga et al, 2005;Kawabe et al, 2005;Mbofung et al, 2007;Enya et al, 2008), and its high levels of nucleotide diversity provide a high degree of discriminatory power useful for isolate identification, results of the present study strongly indicate that the homoplastic evolutionary history of this locus obscures accurate phylogenetic relationships within this complex. Of the relatively small number of genes that have been sampled to date within the FOSC (ex., IGS rDNA, EF-1a, polygalacturonases, mitochondrial small subunit ribosomal RNA, phosphate permease, b-tubulin, nitrate reductase, MAT 1 and MAT2), only the EF-1a and IGS rDNA genes appear to have much phylogenetic signal.…”
Section: Discussionmentioning
confidence: 56%
“…Although the IGS rDNA has become one of the most popular loci for investigating genetic diversity within the FOSC (Fujinaga et al, 2005;Kawabe et al, 2005;Mbofung et al, 2007;Enya et al, 2008), and its high levels of nucleotide diversity provide a high degree of discriminatory power useful for isolate identification, results of the present study strongly indicate that the homoplastic evolutionary history of this locus obscures accurate phylogenetic relationships within this complex. Of the relatively small number of genes that have been sampled to date within the FOSC (ex., IGS rDNA, EF-1a, polygalacturonases, mitochondrial small subunit ribosomal RNA, phosphate permease, b-tubulin, nitrate reductase, MAT 1 and MAT2), only the EF-1a and IGS rDNA genes appear to have much phylogenetic signal.…”
Section: Discussionmentioning
confidence: 56%
“…Moreover, it was revealed that each phylogenetic group in each forma specialis consisted of isolates of one or two VCGs, and the VCGs are distinctive between the groups (Bentley et al 1998;Fernandez et al 1994; Appel and Gordon (1996) Appel and Gordon (1996) FIGS12 GCAAAATTCAATAGTATGGC nt. 1056-1037 bp at F. oxysporum intergenic spacer region, refered to sequences in Appel and Gordon (1996) Appel and Gordon ( Fujinaga et al 2005;Kawabe et al 2005;Kistler 1997;Koenig et al 1997;Manicom and Baayen 1993;Vakalounakis and Fragkiadakis 1999;Mes et al 1994;Woudt et al 1995). In contrast, phylogenetic groups in FOS were composed of VCG0330 and/or 0331 and VCGs did not reflect genetic relationships (Fig.…”
Section: Introductionmentioning
confidence: 79%
“…However, no correlation between the races and genealogical populations has been reported with the exception of F. oxysporum f. sp. lactucae (Shimazu et al 2005;Fujinaga et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The polymorphism of this region was higher than that of other loci, such as the mitochondrial Small Subunit (mtSSU) or the Elongation Factor 1-α (EF) (Mbofung et al 2007), and allowed the genetic diversity detected by VCG in Fusarium oxysporum f. sp. lactucae (Fujinaga et al 2005) to be distinguished.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Fujinaga et al (2005) reported that IGS sequences were a useful indicator of physiological races for F. oxysporum. The polymorphism of this region was higher than that of other loci, such as the mitochondrial Small Subunit (mtSSU) or the Elongation Factor 1-α (EF) (Mbofung et al 2007), and allowed the genetic diversity detected by VCG in Fusarium oxysporum f. sp.…”
Section: Discussionmentioning
confidence: 99%